Efficient proton conductivity of a novel 3D open-framework vanadoborate with [V6B20] architectures. Issue 9 (15th February 2021) - Zhang, Le; Liu, Xinxin; Shang, Mingyu; Sun, Fuxing; Jian, Juan; Bu, Ke; Zeng, Decheng; Yuan, Hongming
Abstract : A novel 3D open-framework vanadoborate exhibits a remarkable proton conductivity of 3.22 × 10 −3 S cm −1 . Abstract : A new three-dimensional (3-D) inorganic metal–oxygen network vanadoborate Na3 H10 [Ni(H2 O)2 (VO)6 (B10 O22 )2 ]·NH4 ·19H2 O (1 ) constructed from lantern-type (VO)6 (B10 O22 )2 clusters, NaO6 polyhedra and NiO6 octahedra, was successfully synthesized by a hydrothermal method. In the structure, the V6 B20 clusters are linked together through NiO6 octahedral bridges, resulting in 1-D chains along the c -axis. The 1-D chains are further connected by NaO6 polyhedra to give rise to a 3-D open-framework structure. Furthermore, lots of NH4 + and H2 O molecules are accommodated in the void of the structure, and may interact with the [V6 B20 ] system via N–H⋯O, O–H⋯O hydrogen bonds, constructing a complex hydrogen-bonding network system. Strikingly, compound 1 exhibited a high proton conductivity of 3.22 × 10 −3 S cm −1 at 50 °C under 100% RH with an activation energy of 1.66 eV.